AN EFFECT OF GEOMETRIC NONLINEARITY ON THE STRESS CONCENTRATION IN A BENDING COMPOSITE STRIP WITH A RECTANGULAR HOLE - Yahnioglu, Nazmiye; Agit, Hakan (YILDIZ TECHNICAL UNIV, 2005)
In this work, under bending of the uniform loading on the upper face of a strip, stress concentration of around the inner rectangular hole is investigated in the framework of the exact geometric non-linear equations of Elasticity Theory in the plane strain-state. Investigations are carried out by helping of Displacement Based Finite Element Methods and Newton-Raphson Method for linearization of system of non-linear equations.
Keywords: Geometric nonlinear; Composite; Hole; Finite Element Methods; Newton-Raphson Method; Engineering